The heparan sulfate editing enzyme Sulf1 plays a novel role in zebrafish VegfA mediated arterial venous identity. - Gorsi, B; Liu, F; Ma, X; Chico, T; v, A; Kramer, K; Bridges, E; Monteiro, R; Harris, A; Patient, R; Stringer, SE (2014)
Arterial and venous specification is critical for establishing and maintaining a functioning vascular system, and defects in key arteriovenous signaling pathways including VEGF (vascular endothelial growth factor) lead to congenital arteriopathies. The activities of VEGF, are in part controlled by heparan sulfate (HS) proteoglycans, significant components of the endothelial glycocalyx. The level of 6-O sulfation on HS polysaccharide chains, that mediate the interaction between HS and VEGFA, is edited at the cell surface by the enzyme SULF1. We investigated the role of sulf1 in vascular development. In zebrafish sulf1 is expressed in the head and tail vasculature, corresponding spatially and temporally with vascular development. Targeted knockdown of sulf1 by antisense morpholinos resulted in severe vascular patterning and maturation defects. 93 % of sulf1 morphants show dysmorphogenesis in arterial development leading to occlusion of the distal aorta and lack of axial and cranial circulation. Co-injection of vegfa165 mRNA rescued circulatory defects. While the genes affecting haematopoiesis are unchanged, expression of several arterial markers downstream of VegfA signalling such as notch and ephrinB2 are severely reduced in the dorsal aorta, with a concomitant increase in expression of the venous markers flt4 in the dorsal aorta of the morphants. Furthermore, in vitro, lack of SULF1 expression downregulates VEGFA-mediated arterial marker expression, confirming that Sulf1 mediates arterial specification by regulating VegfA165 activity. This study provides the first in vivo evidence for the integral role of the endothelial glycocalyx in specifying arterial-venous identity, vascular patterning and arterial integrity, and will help to better understand congenital arteriopathies.